Water Pump System with PV Solar Tracking - Abdullah, Fatin Najiha; Sahari, Norain (Progress in Engineering Application and Technology, 2021)
Solar energy is an essential resource for renewable energy. Solar tracking encourages intense solar energy to produce from the solar panel and allows the sun’s rays to maintain a profile. The purpose of this project is to increase the amount of available energy by using a computerized tracking system to capture the solar rays’ maximum intensity. This project uses solar tracking to build an automatic water pumping system. The rapidly growing demand for energy calls for fossil fuel substitutes. Renewable energy sources show an outstanding figure for generating electricity without using any coal. Water Pump System with PV Solar Tracking can be used for water supply or irrigation. The diesel-powered pumping system has a low cost of capital, but maintenance and service are costly and troublesome. On the other hand, the solar-powered pumping system is quite the opposite. The initial price is high, but running is considerably cheaper. A properly designed solar pumping will be efficient, simple, and reliable. This system should be cost-effective and will meet industrial water needs.